2022
DOI: 10.3389/fmars.2022.920480
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Tidal Marsh Under Very High Flow Velocities and Implications for Nature-Based Flood Defense

Abstract: Nature-based strategies, such as wave attenuation by tidal marshes, are increasingly proposed as a complement to mitigate the risks of failure of engineered flood defense structures such as levees. However, recent analysis of historic coastal storms revealed smaller dike breach dimensions if there were natural, high tidal marshes in front of the dikes. Since tidal marshes naturally only experience weak flow velocities (~0-0.3 ms-1 during normal spring tides), we lack direct observations on the stability of tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 112 publications
1
14
0
Order By: Relevance
“…It should be further investigated if the different phenological states have an impact on biogeomorphology. Previous studies have already shown that below-ground effects of rootsoil interaction are important for energy reduction due to shoaling and erosion reduction (Alam et al, 2018;Redelstein et al, 2018;Kosmalla et al, 2022;Schoutens et al, 2022). This study therefore proposes to include above-ground plant state for future investigations on above as well as below-ground biomass.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It should be further investigated if the different phenological states have an impact on biogeomorphology. Previous studies have already shown that below-ground effects of rootsoil interaction are important for energy reduction due to shoaling and erosion reduction (Alam et al, 2018;Redelstein et al, 2018;Kosmalla et al, 2022;Schoutens et al, 2022). This study therefore proposes to include above-ground plant state for future investigations on above as well as below-ground biomass.…”
Section: Discussionmentioning
confidence: 95%
“…Ecosystem-based coastal defenses (Schoonees et al, 2019) provide multiple ecosystem services (European Commission and Directorate-General for Environment, 2014;Haines-Young and Potschin, 2018), enhancing their environmental value while bolstering natural resilience (Bouma et al, 2014;Doswald et al, 2014). Salt marshes, taking reference to various globally distributed sites (Mcowen et al, 2017), have been studied in laboratories and in the field to evaluate multiple ecosystem services, like the absorption of hydrodynamic energy (Ghisalberti and Nepf, 2006;Augustin et al, 2009;Ysebaert et al, 2011;Koftis et al, 2013;Anderson and Smith, 2014;Möller et al, 2014;Carus et al, 2016;Vuik et al, 2016;Rupprecht et al, 2017;Lou et al, 2018;Garzon et al, 2019;van Veelen et al, 2020;Willemsen et al, 2020;Keimer et al, 2021;Zhang et al, 2022), sediment accretion (Christiansen et al, 2000;Cahoon et al, 2006;Andersen et al, 2011;Baaij et al, 2021;Cahoon et al, 2021;Proenca et al, 2021), soil stabilization (Ford et al, 2016;Kosmalla et al, 2022;Schoutens et al, 2022) and geomorphological changes Chen et al, 2020;Cao et al, 2021;Ladd et al, 2021).The above-mentioned effects depend on vegetation species, traits of the above-and below-ground biomass and hydrodynamic conditions (Schoutens et al, 2020). Integrating and upscaling the presence of salt marshes into coastal protection plans, thus, adds multiple protection funct...…”
Section: Introductionmentioning
confidence: 99%
“…In relation to managed realignment there is a practical advantage. Sod removal lowers the elevation of high elevated foreshores that would otherwise limit water flow into the realignment site (van den Berg et al, in prep; Schoutens et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The flow flumes were constructed from the dike crest, along the outer slope to the dike toe and on the tidal marsh. Schoutens et al (2022) measured soil and vegetation characteristics at the tidal marsh 50 m North of the experimental site at end of January 2021 (Figure 1D). In this study we adopt their results, based on the assumption that in the proximity of this location, soil and vegetation conditions are also representative of our site.…”
Section: Experimental Sitementioning
confidence: 99%